Empowerment of Angkul-Angkul Culinary Sellers with Ergo-Entrepreneurship Oriented Improving of Entrepreneurship and Concern on Environmental Attitude - Sutajaya, I Made; Ristiati, Ni Putu; Sukra Warpala, I Wayan (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 6 No 2 (2020): Volume 6 No 2 Desember 2020DO - 10.24843/JEI.2020.v06.i02.p08, 2020)
The culinary delights that are sold in front of the house entrance gate ( angkul-angkul ) are currently starting to develop rapidly in Peliatan Village, Ubud, Gianyar, Bali. The research objectives are: (1) to prove that empowerment of angkul-angkul culinary ergo-entrepreneurship oriented can improve entrepreneurial and environmental care attitudes and (2) to know how to solve ergonomic and entrepreneurial problems faced by culinary sellers. This quasi-experimental research used the same subject design. The subjects were 25 angkul-angkul culinary sellers who were randomly selected from 37 available populations. The independent variable in this study is the empowerment of angkul-angkul culinary with ergo-entrepreneurship orientation. The dependent variable is an entrepreneurial attitude and an environmental care attitude which is recorded before and after empowerment. The data obtained were analyzed using paired t test at a significance level of 5%, because the data were normally distributed. The results showed that the entrepreneurial attitude of sellers increased by 20.13% and the attitude of caring for the environment increased by 20.01% and the obstacles faced related to the empowerment of sellers were more technical and economic in nature which could be overcome through awareness programs. The conclusion is that the empowerment of angkul-angkul culinary with ergo-entrepreneurship orientation can significantly improve entrepreneurial attitudes and environmental care attitudes (p <0.05).